Implementasi Digital Marketing Dalam Pemasaran Pariwisata Hutan Kota “Punti Kayu” Di Palembang - Agus Yusrizal Bakri; Loren Diaz Lintang; Juwita Puja Anggraini; Tata Sutabri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Tourism is now a sector that is experiencing rapid growth supported by developments in information and communication technology. One of the potential tourism destinations in Palembang is the "Punti Kayu" City Forest. However, marketing is still less than optimal. This research aims to explore the implementation of digital marketing in increasing tourist visits to the "Punti Kayu" City Forest. Through a qualitative approach, data is collected through observation, interviews and documentation studies. The results show that digital marketing plays an important role in increasing the visibility of the "Punti Kayu" City Forest in the eyes of the public, especially the younger generation. Social media content strategies, promotion through influencers, and search engine optimization (SEO) are implemented to increase brand awareness and visits. Obstacles such as lack of resources and training become obstacles in its implementation. However, with cooperation between stakeholders and the use of appropriate technology, the potential of the "Punti Kayu" City Forest as a leading tourist destination in Palembang can be achieved. The implementation of digital marketing in tourism marketing for the "Punti Kayu" City Forest shows that technological adaptation in the tourism sector is a necessity in the current digital era.